Agama, seks & kekuasaan : Kumpulan tulisan, 1979-2012 / Julia Suryakusuma; Penerjemah, Tam Notosusanto [et.all]; Penyunting, Imelda Bachtiar dan Julia Suryakusuma - SURYAKUSUMA, Julia; TAM Notosusanto; IMELDA Bachtiar; SURYAKUSUMA, Julia (Komunitas Bambu, 2012)
xlvi, 470 hlm. : Ilus. ; 21 cm.